Switzerland : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
The Article IV Consultation discusses the IMF Executive Board's assessment of economic developments and policies in Switzerland. With the exchange rate floor in place for more than one year, the Swiss economy has been relatively stable. Although overall export growth is weak, the external position remains comfortable, reflecting high investment income and strong export performance in some sectors. Executive Directors noted that, notwithstanding Switzerland's stable economy and strong policy frameworks, risks stemming mostly from the euro area crisis and vulnerabilities in the domestic financial sector have clouded the near-term outlook.